Risk assessment of added chemicals in plastics in the Danish marine environment. (August 2020) - Fauser, Patrik; Strand, Jakob; Vorkamp, Katrin
Abstract: A risk assessment framework for direct exposure of residual additives and monomers present in ingested plastic particles, including microplastics, in the Danish marine environment, was presented. Eight cases of different polymer types and product groups were defined that represent the most significant exposures, and thus potential high-risk cases, towards marine organisms. Risk Quotients (RQ) were calculated for three trophic levels, i.e. pelagic/planktonic zooplankton: copepod, benthopelagic fish: Atlantic cod and seabird: northern fulmar. European and Danish Environmental Quality Standard (EQS) values were used as Predicted No-Effect Concentrations (PNEC). RQ larger than unity, indicating potential risks, were found for copepod and cod (pelagic community) and the flame-retardant pentabromodiphenyl ether (PeBDE) used in polyurethane (PUR), the biocide tributyltin (TBT) present as impurity in polyvinylchloride (PVC) and PUR, and the flame-retardant hexabromocyclododecane (HBCDD) used in expanded polystyrene (EPS). A potential risk was found for fulmar (secondary poisoning) and PeBDE used in PUR. Highlights: Eight cases of relevant plastic pollution in the Danish environment were identified. Potential risks were found for three chemicals and two marine pelagic species. Chemicals with increased risks were brominated flame-retardants (BFR) and tributyltin. Potential risks were found for a BFR and secondary poisoning of seabirds. The availability of Predicted No-Effect Concentrations limits the risk assessment.